Convergence of Narcissism Measures From the Perspective of General Personality Functioning - Samuel, Douglas B.; Widiger, Thomas A. (Assessment (Odessa, Fla.), 2008)
The construct of narcissism has a lengthy history and has been operationalized and measured by a variety of instruments. In this study, five narcissism scales were compared in terms of alternative conceptualizations of narcissism offered by C. C. Morf and F. Rhodewalt (2001), D. L. Paulhus (2001), and S. Vazire and D. C. Funder (2006), using the domains and facets of the five-factor model as a common point of comparison. The findings provided little support for the conceptualizations of Morf and Rhodewalt or Vazire and Funder. Support was obtained for the conceptualization of Paulhus, particularly as assessed by the Narcissistic Personality Inventory and, secondarily, the Millon Clinical Multiaxial Inventory—III. Implications for the assessment and conceptualization of narcissism are discussed.